Sistem Pendukung Keputusan Pemilihan Guru Berprestasi Menggunakan Metode Profile Matching Pada SMK Insan Global - Maruloh Maruloh; Fitri Puji Lestari; Ahmad Setiadi; Norma Yunita (Sekolah Tinggi Teknologi Informasi NIIT, 2020)
The teacher is the most important milestone in advancing education, is considered as someone who can inspire, motivate and the most important role is to influence the quality of education of students in school. However, in the Global Insan Vocational School the process of selecting outstanding teachers is still subjective, because it is only based on the assessment of the principal and is not based on certain criteria for the process of selecting outstanding teachers so that it causes injustice between one teacher and another and is not well targeted. The criteria for selecting outstanding teachers in Global Insan Vocational Schools is the aspect of discipline, aspects of teacher performance, aspects of integrity, and aspects of behavior. In calculating the writer using the Profile matching method, which is a research method that can be used in decision support systems, the process of evaluating competencies is carried out by comparing one value profile (the value of competency needs) with several other competency value profiles, so that the results of the difference between competency needs can be known. needed, the difference between competencies is called a gap, where the smaller gap has a higher value. The aspects used in this study are Discipline, Teacher Performance, Integrity, and Behavior. Where every aspect has criteria as their choice